Návrh zlepšení marketingového mixu společnosti AUDIFIED - Semler, Josef (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Bakalářská práce se zabývá návrhem na zdokonalení marketingového mixu společnosti softwarové divize společnosti AUDIFIED s.r.o. V teoretické části jsou přiblíženy pojmy pro vypracování praktické části práce. V analytické části jsou provedeny analýzy vnitřního a vnějšího prostředí společnosti a jsou shrnuty ve SWOT analýze. Návrhy na zlepšení současného stavu vychází z analýzy současného stavu.

The bachelor thesis deals with a proposal for improving the marketing mix of the company's software division AUDIFIED s.r.o. In the theoretical part the concepts for the practical part of the thesis are presented. In the analytical part, internal and external analyses are performed, which are summarized in the SWOT analysis. Suggestions for improvement of the current situation are based on the analysis of the current situation.
Proposal to improve the marketing mix of the company AUDIFIED
Keywords: marketing; marketingový mix; online marketing; swot analýza; marketingová komunikace; marketing; marketing mix; online marketing; swot analysis; marketing communication